Designing Ambidextrous AI Governance for Digital Transformation in Fintech Sector - Lestari, Merryana; Wijaya, Agustinus Fritz; Puspita, Maria Entina; Vicky (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
The rapid integration of Artificial Intelligence (AI) in financial technology (fintech) has created an urgent need for robust governance mechanisms. While AI drives digital transformation by enabling automation, personalization, fraud detection, and operational efficiency, it also introduces critical challenges related to ethics, security, transparency, and regulatory compliance. This study proposes an Ambidextrous AI Governance Framework, grounded in the COBIT 2019 framework, to address these challenges in fintech organizations. The framework balances exploration (innovation, agility, and ethical practices) with exploitation (risk control, compliance, and operational efficiency) through five integrated governance layers: Governance, Strategic Alignment, Ambidextrous, Operational, and Compliance & Assurance. A design science research approach was employed, including a literature review, expert validation, and simulation within a controlled fintech environment. The results showed that the proposed framework improved governance maturity across COBIT domains and embedded principles of trustworthy AI, such as transparency, accountability, and fairness. This research provides a scalable and adaptable model aligned with international standards, such as ISO/IEC 42001, and regulatory frameworks, including the EU AI Act and OJK guidelines. The proposed governance design enables fintech organizations to innovate responsibly while mitigating risks, ensuring compliance, and fostering trust in AI-driven financial services.